IMPLEMENTASI PROGRAM KELUARGA HARAPAN DILIHAT DARI ASPEK KOMUNIKASI PADA DESA MANGKUSIP KECAMATAN TANTA KABUPATEN TABALONG (JAPB, 2022)
This study aimed to determine and analyze the implementation of the Family Hope Program (PKH) in terms of communication aspects in Mangkusip Village, Tanta District, Tabalon Regency. A qualitative research method examines natural objects where the researcher is the key instrument. The subjects in this study were individual resource persons consisting of 2 village officials as implementers and providers of facilities to facilitate the running of the program and three community members as beneficiaries of assistance from PKH, which the program targets for their children who are still in school in the research which is used as a source of helpful information. Accurate. The type of research used by the author in this study is descriptive, with a qualitative approach taken from the steps of data collection through observation, interviews, and documentation. The sampling technique used is purposive sampling (a purposeful sampling technique) which is a sampling technique that is used intentionally or refers directly to people who are considered to represent the characteristics of the population. Primary data sources were obtained from observations and interviews, while secondary data were obtained from the documentation. The research variable is seen from the communication aspect, where the researcher uses the theory according to Edward III, namely three indicators that can measure the success of implementing the communication variable: transmission, clarity, and consistency. The data analysis method used is analysis, according to Miles and Hubberman. The results of this study indicate that the Implementation of the Family Hope Program (PKH) at the Mangkusip Village Office, Tanta District, Tabalong Regency, is categorized as implemented. Keywors: Implementation, Family Hope Program, Communication Aspect